Implicit Transfers in IMF Lending, 1973-2003 - Joshi, Priyadarshani (IMF Working Papers; Working Paper ;, 2005)
We compute realized transfers implicit in IMF lending from 1973-2003, based on 2003 IMF repayment projections and promised debt relief. IMF lending rates to high-and middleincome countries fell short of industrial country borrowing rates by 30-150 basis points over the period as a whole, but exhibited a small premium after 1987. The subsidy received by low-income and HIPC countries was much higher (400-600 basis points, respectively). In 2002 NPV terms, cumulative transfers were 12-15 percent of 2002 GDP for the HIPCs, 2-3 percent for low income countries, and less than 3/4 percent for the emerging market countries.